Studies on western Pacific gorgonians (Anthozoa: Octocorallia, Chrysogorgiidae). Part 1: a review of the genus Chrysogorgia, with description of a new genus and three new species - Xu, Yu; Zhan, Zifeng; Xu, Kuidong (Zootaxa, 2023)
Members of Chrysogorgia Duchassaing & Michelotti, 1864, known as golden corals, are distributed in the deep sea worldwide. Based on specimens obtained from the tropical western Pacific and an integrated morphological-molecular approach, we established a new genus Parachrysogorgia, which includes 13 species separated from Chrysogorgia, and described nine species of Chrysogorgia including three new species C. arboriformis sp. nov., C. cylindrata sp. nov. and C. tenuis sp. nov., and two new combinations of Parachrysogorgia. The genus differs from Chrysogorgia by possessing a bare, sclerite-free area at the base of each tentacle and eight distinct projections beneath tentacles. Chrysogorgia cylindrata sp. nov. is distinguished by a slender bottlebrush-shaped colony in adults, elongate and lobed scales in coenenchyme, and warty and thick sclerites near the polyp mouth area. Chrysogorgia arboriformis sp. nov. is characterized by a tree-shaped colony with a long unbranched stem, slender and thin scales usually with large warts in coenenchyme. Chrysogorgia tenuis sp. nov. can be separated by a broad bottlebrush-shaped colony, long interbranch distance, elongate scales with broad lobes in polyp body wall. In contrast to the intraspecific variation of colony form, branch internodes, branching sequence and polyps, the sclerite forms and arrangement in different parts can be viewed as the most important character to separate Chrysogorgia species. For convenient identification, we divided the Chrysogorgia species into 12 morphological groups and divided Parachrysogorgia into three groups based on their sclerite forms and arrangement.